2016
DOI: 10.1007/s00221-016-4703-8
|View full text |Cite
|
Sign up to set email alerts
|

The motor and the brake of the trailing leg in human walking: leg force control through ankle modulation and knee covariance

Abstract: Human walking is a complex task, and we lack a complete understanding of how the neuromuscular system organizes its numerous muscles and joints to achieve consistent and efficient walking mechanics. Focused control of select influential task-level variables may simplify the higher-level control of steady state walking and reduce demand on the neuromuscular system. As trailing leg power generation and force application can affect the mechanical efficiency of step-to-step transitions, we investigated how joint t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…We calculated joint moments with custom inverse dynamics Matlab code (Toney, Chang, 2013; Toney, Chang, 2016), using included joint angles for the ankle and knee and the thigh segment angle for the hip. We calculated joint work over STS, pendular phase, and full stance phase.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated joint moments with custom inverse dynamics Matlab code (Toney, Chang, 2013; Toney, Chang, 2016), using included joint angles for the ankle and knee and the thigh segment angle for the hip. We calculated joint work over STS, pendular phase, and full stance phase.…”
Section: Methodsmentioning
confidence: 99%
“…For example, during postural balance tasks, humans have been observed to regulate COMrelated behavior through coordination of lower-level structures including joints and muscles (Nashner, 1977;Nashner and McCollum, 1985;Ting and Macpherson, 2005;Torres-Oviedo et al, 2006). Joint-mediated control of whole-limb mechanics (which are closely linked to COM mechanics) has also been observed both in unperturbed human walking (conserved limb power; Toney and Chang, 2016) and after peripheral nerve injury in walking cats and rodents (conserved limb trajectories; Bauman and Chang, 2013;Chang et al, 2009). Panizzolo et al (2017) likewise showed that individual joint mechanics (ankle, knee, hip) adapt to various unanticipated terrain disturbances in ways that maintain total positive mechanical work of the lower limb, irrespective of the type of perturbation.…”
Section: Com Versus Peripheral ( Joint) Mechanical Conservationmentioning
confidence: 99%
“…Toward this fundamental understanding, we opted to include and report external mechanical work performed on the body's CoM by forces exerted by the individual legs during walking as a complement to joint-level measures derived using inverse dynamics. Indeed, as one example, power generated at the ankle can be offset via changes in power absorption at other joints (Toney and Chang, 2016), motivating the need for limb-level analysis. However, we acknowledge that some authors have questioned the utility of those outcome measures to provide direct insight into muscle function and factors that affect walking economy and that this remains debated (Kuo and Donelan, 2009;Neptune et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to gain insight into how individual joint mechanics altered center of mass (CoM) mechanics, we used the individual limbs method (Donelan et al, 2002) and measured GRF data to estimate positive and negative mechanical work performed on the CoM by the leading and trailing legs during double support and the stance leg during single support. For example, power generated at the ankle can be offset via changes in power absorption at other joints (Toney and Chang, 2016), motivating our inclusion of this limb-level analysis. Specifically, we derived the CoM power curves as the dot product of CoM velocity and the sum of the individual limbs GRF using previously published procedures (Donelan et al, 2002) and integrated those curves with respect to time.…”
Section: Measurement and Analysismentioning
confidence: 99%